The RAPE- Central Region: an associative model focused on territorial competitiveness (2016)
The RAPE Central Region is the first regional platform in the country, identifying as one of its main axes competitiveness to generate economic development, the research proposes the use of the tool of the Contract Plan as an instrument to generate competitive advantages, promoting economic activities that make up the largest share of GDP, as is agriculture, resulting in investment in projects that promote training and the use of new technologies to improve agro-industrial processes in the region, reducing social gaps and economic presenting the Colombian population.